Komunikasi Kesehatan Perkumpulan Keluarga Berencana Indonesia (Pkbi) Daerah Riau Dalam Menjaga Kesehatan Reproduksi Di Lembaga Pembinaan Khusus Anak - nazhifah, nazhifah (Jurnal Paradigma, 2023)
Abstract This study examines how the form of health communication carried out by PKBI in maintaining adolescent reproductive health in LPKA. This research uses a descriptive qualitative approach using social understanding theory. The determination of informants was determined by purposive sampling with a total of four people. Data collection methods by observation, interviews. The results showed that health communication is influenced by three aspects, namely Input, Process and Output. Input, STAR PKBI provides skills training to increase capacity for its volunteers before going to the field and process, in this case STAR PKBI does it by using interpersonal communication strategies through the provision of Kespro health education materials. The same thing in PKBI maintains this information so that LPKA children can understand by always being consistent in providing information conveyed related to kespro and on the Output side, namely there is a change in knowledge, attitudes, and behavior, it is clear that PKBI conducts health communication in maintaining the reproductive health of LPKA children, it does explain about kesro to LPKA there is a change in knowledge from those who do not know to know.Keywords : Health Communication, Reproductive Health, LPKA